A study on poverty concepts and perspectives: conceptual paper - Kasim Md Mansur; Remali Yusoff; Rosazman Hussin; Rasid Mail (BIMP-EAGA Unit for Tourism Development (BE-UTD), 2013)
The concept of poverty is subjective and it varies in many perspectives based on the indicators used. The objective of the study is to determine the concept and definition of poverty through exploring the collection of poverty definitions from different sources in order to set its own standardized of operational poverty definitions. This exploratory study will be based on qualitative research methodology. The output of study provides with a clear concept of poverty definition.